2012
DOI: 10.1152/ajpendo.00209.2012
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod regulates dietary preferences and energy metabolism in young developing Fischer 344 rats but not in same-age Wistar rats

Abstract: The effects of photoperiod on dietary preference were examined using young growing Fischer 344 and Wistar rats, which are seasonal and nonseasonal breeders, respectively. Rats were provided a low-fat, high-carbohydrate diet (LFD: 66/10/24% energy as carbohydrate/fat/protein) and high-fat, low-carbohydrate diet (HFD: 21/55/24% energy as carbohydrate/fat/protein) simultaneously under long- (LD: 16 h light/day) and short-day (SD: 8 h light/day) conditions for 3 wk. Fischer 344 rats preferred the LFD to the HFD un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
4
15
1
Order By: Relevance
“…The effect of photoperiod, but not HFD, on serum IGF-1 levels, is consistent with this effect on lean mass. When fed a HFD, F344 rats adjust food and protein intake downward, as also observed by Togo et al [ 25 ]. This suggests that F344 rats attempt to balance their food intake in terms of energy with the macronutrient (protein) requirements for growth.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The effect of photoperiod, but not HFD, on serum IGF-1 levels, is consistent with this effect on lean mass. When fed a HFD, F344 rats adjust food and protein intake downward, as also observed by Togo et al [ 25 ]. This suggests that F344 rats attempt to balance their food intake in terms of energy with the macronutrient (protein) requirements for growth.…”
Section: Discussionsupporting
confidence: 70%
“…Juvenile F344 rats gain less weight on short photoperiod than on long photoperiod [ 24 , 7 ], and so might be predicted to be resistant to diet-induced obesity. A recent study of F344 rats, which were fed a very high fat diet, supports this prediction, based on epididymal fat and leptin levels [ 25 ]. However in this study, a more comprehensive assessment of body composition has been used and we show that photoperiodically-sensitive F344 rats are susceptible to diet-induced obesity.…”
Section: Introductionmentioning
confidence: 80%
“…These changes were dependent on the photoperiod, because only the animals that ate orange in the short day had their parameters altered, but it was also dependent on the season in which the fruit was harvested, because no differences were obtained with the orange from the northern hemisphere. Numerous studies in small rodents have shown that a long photoperiod increases fat accumulation or body weight, while the opposite was observed for a short photoperiod [30][31][32][33][34]. Our data show a similar effect on OSSD animals, which are in a short photoperiod but consuming fruit harvested in the spring.…”
Section: Discussionsupporting
confidence: 65%
“…The reason why rodents increase their body mass in an LD photoperiod is not fully understood. Some authors report an increase in calorie intake or a change in diet preferences with longer photoperiods [31,32], while other studies attribute the changes to a decrease in BAT activity [35] or to activation of WAT lipolysis and browning during the SD [33]. In our study, the possibility of an increase in the fat content of the OSSD group due to diet was discarded, because no significant changes were observed in food intake or plasmatic parameters.…”
Section: Discussionmentioning
confidence: 76%
“…validated qPCR primers as used in the present study) than other photoperiodic species, the use of rats simplifies both the experimental design and the laboratory work. In addition, one strong advantage to using F344 rats as an experimental model of photoperiodism is that they provide a good system for comparing the results with nonseasonal rodents, as seen in recent studies on the hypothalamic-pituitary-adrenal axis ( 24 ) and circadian rhythms ( 23 ), as well as on food selection and the mechanisms underlying energy metabolism ( 45 ).…”
Section: Discussionmentioning
confidence: 99%